Poland Housing Finance Policy Note - Chiquier, Loїc (World Bank, Washington, DC, 2021)
This policy note is part of a World Bank targeted study on the prospects for development of the financial services industry in Poland. The report discusses the evolution of housing loans, affordability of housing loans, risk management and regulations (particularly the development of mortgage insurance products, hard-currency denominated mortgage loans, consumer information, and appraisal norms and capital adequacy rules), accessing bond markets (including the legal and regulatory framework for securitization), and rental finance.